The Role of using smartphone applications in developing creative thinking among first-grade secondary students in the course of computer - Asiri, Abdulmajeed Mohamad (Journal of Educational and Psychological Sciences, 2021)
The present research aimed to identify the role of using smartphone applications in developing the creative thinking skills among students in the first grade of secondary education in the computer course. The descriptive and analytical approach was adopted, and the research tool was represented in the questionnaire. The research population included all the first-grade students of Abha Department of Education in Asir region, which amounted to (367) students. About (88) students were randomly chosen. The research concluded several conclusions, the most important of which is that there is a role for using smartphone applications in developing the skill of (fluency) among students in the first grade of secondary education in the computer course with relative weight (71.2%), developing the skill of (Flexibility) with relative weight (70.2%), developing the skill of (originality) with relative weight (77.2%), and developing the skill of (brainstorming) with relative weight (73.8%). The researcher recommended the necessity of using smartphone applications because they are one of the most important sources for building, strengthening and developing creative thinking skills in the educational environment in which the education department operates, and increasing interest in these applications by examining the experiences of developed countries and making use of them in the best way possible, and preparing training programs required to increase awareness among students in the first grade of secondary education of the importance of using smartphone applications and their relationship to developing creative thinking skills.